Argumentation Skills in Physisc Implementation: A Systematic Literature Review - Triananda, Lucy; Kuswanto, Heru; Jumadi, Jumadi (STKIP Singkawang, 2025)
The aim of this study are to analyze and describe the reasoning skills of students from primary school until college in understanding the learning concept and application of physics. This research focuses on the factors that influence students' concept understanding and argumentation skills in physics. The research method used was systematic literature review (SLR), a literature study in which data was collected through various published articles relevant to reasoning skills in physics from 2019 to 2023. The implementation of this research was done by collecting data through scientific articles published and indexed in the Scopus database. The data analysis technique used is the PRISMA flowchart with different levels and the VOSviewer application. The results showed that the factors effecting argumentation ability in learning physics are influenced by the learning model used, the learning approach, the way the teacher guides the learning activities, as well as environmental factors and community life.